HISTORICAL AND MODERN ASPECTS OF RUSSIAN PEDIATRIC VITAMINOLOGY - O.A. Gromova (Педиатрическая фармакология)
The article describes the history of establishment of vitaminology as a science in Russia. Properties of vitamins and microelements determining the necessity of their presence in the organism and states which develop in case of their deficiency, are described in a transparent and clear form. The main part of the article is devoted to replacement of vitamins and microelements in case of their insufficient content level in the organism. It is the field of medicine where Albert imre szent gyorgyi's words: «capabilities induce the need to use these capabilities…» are especially relevant.Key words: vitamins, microelements, properties, need, deficiency, treatment, children.